Rural Poverty: Old Challenges in New Contexts. - Dercon, S (GPRG, 2008)
Poverty is still a predominantly rural phenomenon. However, the context of rural poverty has been changing across the world, with high growth in some economies and stagnation in others. Furthermore, increased openness in many economies has affected the specific role of agricultural growth for rural poverty reduction. This paper revisits an ‘old’ question: how does growth and poverty reduction come about if most of the poor live in rural areas, dependent on agriculture? What is the role of agricultural and rural development in this respect? Focusing on sub-Saharan Africa, we use theory and the available evidence to conclude that changing contexts has meant that agricultural growth is only in particular settings crucial as an engine for growth, more specifically in landlocked, resource poor countries, which are often also characterised by relatively low potential for agriculture. However, extensive market failures in key factor markets and likely spatial effects give a remaining crucial role for rural development policies, including focusing on agriculture, to assist the inclusion of the rural poor in growth and development. How to overcome these market failures remains nevertheless a key issue for further research and evaluation.